A novel arc suppression method based on active voltage control. (December 2022) - Bai, Hao; Li, Xu; Zou, Yu; Li, Minghu
Abstract: The passive current arc-suppression cannot compensate the active and harmonic components, active current arc-suppression has poor reliability and economy, the passive voltage arc-suppression is easy to enlarge the fault range. The paper analyses the essential mechanism of ground fault arcing, proposes a novel active voltage arc suppression technology. The method adjusts the fault phase voltage by changing different winding numbers of grounding transformer. The fault phase voltage drops below the arc restriking voltage critical point to realize active arc suppression. A typical 10 kV distribution network is used to verify the proposed method.